(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Skill acquisition is a growing concern in Nigeria due to socio-economic circumstances and a glut in the labour market which predisposes people to alternatives such as self-employment and a refocus on the care for the environment. Diverse by-products of the self-employed artisans have varied effects on the environment, hence the need to establish how their training affects their environmental practices. The study is a descriptive survey of learners and facilitators in five skill set areas from different skill acquisition programmes in Lagos. The research set out to document the nature of waste output and level of environmental awareness of the participants and facilitators, as well as the effect of training on environmental practices. The study was premised on Botha and Atkins’ (2005) theory of adoption of innovation. Three research questions on artisans’ typical output, disposal practices, and effect on the environment, along with the influence of facilitators’ training guided the study. A total of 250 participants were selected using stratified and proportionate random sampling techniques. The Questionnaire, Key Informant Interview sessions, and Observation Schedule were used for data collection and analysed quantitatively and qualitatively using descriptive statistics and content analysis. Findings revealed a low level of incorporation of environmental awareness into skill training programmes and the gap in teacher training. It was recommended that both adult learners and facilitators be appropriately trained and equipped to effectively tackle 21st-century problems.